Breast Reconstruction: Effects on Body Image Following Surgery - Anglin, Laura (My University, 2017)
Women undergoing breast reconstruction are susceptible to many consequences from this process including negative implications on the female psyche related to body image. This project assessed the satisfaction women had with their breast and body image before and after breast reconstruction. Demographic and characteristic data were also recorded. All of the participants were women undergoing surgical treatment for breast cancer. The influence breast reconstruction had on participants’ body image was evaluated using two validated tools. Questionnaires were distributed prior to and 4 to 8 weeks after breast reconstruction. The findings indicated that breast reconstruction negatively impacted half of the participants. Due to the small sample size used in this pilot project, trends related to participant characteristics and body image were not established, although some correlations were found. Findings from this work indicates future research should focus on: a) determining what common characteristics exist among women who suffer with their body image after breast reconstruction; b) developing a standardized tool to screen breast reconstruction patients for body image disruptions; and c) establishing what steps plastic surgery personnel should take to provide their patients with effective treatment when a patient does experience body image disturbances. The findings from this project will be used to educate healthcare providers who work with the breast cancer population on possible body image consequences their patients are subject to experiencing. The quality and consistency of preoperative education will also be assessed, as responses regarding the need for more pre-operative education varied. The ultimate goal is that this work will positively impact the quality of life for women after breast reconstruction.
Keywords: breast reconstruction; body image; breast cancer patients